Division of Tasks Using the Hungarian Method - Irsyadi Zain; Y Rahmat Akbar (Journal of Business and Management Review, 2022)
Optimization is the process of optimizing existing resources in order to obtain effective and efficient results. The maximum division of tasks is when each employee does one job at a time. The division of work needs to be seriously handled so that every employee gets the maximum wage according to the working hours determined by the company. This research was conducted in the Rumah Jahit Nia, Sewing House industry in Pekanbaru City, Riau Province, Indonesia. The purpose of this study is that the company can divide each worker’s tasks to minimize the budget expenditure for paying overtime salaries so that the sources of financing and time used to complete the work are minimized. The research design uses quantitative data with applied research. The analysis method uses an assignment model with the Hungarian method. The completion of the Hungarian method is that the number of employees employed must be equal to the number of jobs that must be completed. In this study, the data source is seven employees with seven jobs to produce the minimum total financing. The study results obtained minimal financing with one employee doing one job. The minimization optimization results are Operator A, assignment IV financing Rp.13,333,-; Operator B, assignment VII with the financing of IDR 20,000; Operator C, assignment VI, financing Rp. 30,000, -; Operator D, assignment III with the financing of Rp. 25,333,-; Operator E, assignment I financing Rp. 25,000, - ; Operator F, assignment V financing Rp. 42,000, - ; Operator G, assignment II financing Rp.33,750,- Total minimum financing Rp.189,416,-.